HIV Screening and Awareness Survey for Pregnant Women in a Remote Area in Xinjiang Uyghur Autonomous Region of China - Sun, Yuping; Hewan-Lowe, Karlene; Wu, Qiang; Yu, Jiang; Guo, Zhiqiu; Han, Yali; Fan, Yujiang; Qin, Xianfang; Xu, Ping; Bolatihan, Janati; Hoshaerbai, Mayinuer; Yuan, Luping; et al. (My University, 2011)
Objective: The number of people infected with human immunodeficiency virus (HIV) in China has increased in recent years. HIV screening for pregnant women was performed in a remote area in Xinjiang, as an effort to promote universal HIV screening in pregnant women and to help prevention of mother-to-child transmission. Methods: Pregnant women in Burqin and Jeminay Counties in Xinjiang were offered free voluntary HIV screening. Local mid-level medical workers were trained to use Determine® HIV-1/2 kit for HIV screening. All the tested pregnant women signed a consent form, received HIV education material, and participated in an HIV knowledge survey. Results: All the 890 pregnant women receiving HIV test had negative result. Among these women, 67.6% were Kazakh and 40.9% were farmers. Survey of HIV knowledge showed that these women's awareness about mother-to-child transmission was limited. The levels of HIV knowledge were related with ethnic background, age, education and profession of the pregnant women. Conclusion: The results suggested that HIV infection had not become a significant problem among the pregnant women in this remote area of Xinjiang, but continued efforts to improve the awareness of HIV, especially the knowledge about mother-to-child transmission of HIV, in pregnant women were needed.
Keywords: Universal HIV screen; pregnant women; mother-to-child transmission